Malware Detection in Cloud Environment (MDCE) - El-Khouly, Mahmoud M.; Abou El-Seoud, Samir (International Journal of Interactive Mobile Technologies (iJIM), 2017)
Since cloud computing technology is growing day by day, it comes with many security problems, especially from threats such as malware. As more services migrate to the cloud architecture, the cloud will become a more appealing target for cyber criminals. In this paper, we present the current threats to the cloud environment, and the proposed detection systems for malware in the cloud environment. We then present a multiple detection system that is aimed at combating the spread of malware by cloud environment.